The life and work of Che Guevara - Luther, Eric (Alpha, 2001)
Critical Lives: Che Guevara covers his entire life, including: Che's struggle to breathe-the Argentine youth almost crippled by asthma; Doctor Che- from his work in a leper colony to his travels throughout poverty-stricken Latin America; Soldier Che-his days as a doctor for Fidel Castro's troops lead to his joining of the military; Che the revolutionary-a guerrilla in Cuba; Che the intellectual-the renowned speaker/thinker/author also serves as president of Cuba's National Bank; Che's last stand-fomenting revolution in the Congo and Bolivia-and his execution in the Bolivian jungle; Che forever-the cultural icon; and The Return of Che -a hero's re-burial in Cuba and the schoolchildren's declaration: "We will be like Che